Penerapan Aksen Kain Tenun Endek Bali pada Perancangan Chef Knife Bag Multifungsi Berbahan Kulit Sintetis - Nurillah Wendiasih Sitompul; Geggy Gamal Surya (Garina, 2025)
Endek Bali weaving is a distinctive cultural heritage of Bali that has been increasingly applied to various product design elements, including interior accents and fashion media. While the use of Endek fabric has been applied to various bag accents, the integration of traditional fabrics in chef knife bags is still rare, resulting in monotonous designs. This study aims to design a chef knife bag incorporating the Endek Bali motif as part of a multifunctional product design. The chef knife bag not only functions as a bag for carrying kitchen knives but also as a stand or mat for knives during cooking events. This design uses synthetic leather, which closely resembles real leather but is more affordable and environmentally friendly. By incorporating the Endek Bali motif into this design, it is hoped that it will introduce Balinese culture to the global stage, particularly in the culinary and creative industries. Furthermore, this design offers a practical solution for culinary professionals who need easy-to-carry and functional tools for attending cooking events or competitions. Through this design, it is expected to enhance aesthetic value while supporting the preservation of Indonesian culture.